2012
DOI: 10.1515/iral-2012-0010
|View full text |Cite
|
Sign up to set email alerts
|

What word-level knowledge can adult learners acquire after minimal exposure to a new language?

Abstract: Discussions about the adult L2 learning capacity often take as their starting point stages where considerable L2 knowledge has already been accumulated. This paper probes the absolute earliest stages of learning and investigates what lexical knowledge adult learners can extract from complex, continuous speech in an unknown language after minimal exposure and without any help. Dutch participants were exposed to naturalistic but controlled audiovisual input in Mandarin Chinese, in which item frequency and gestur… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
41
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 0 publications
4
41
1
Order By: Relevance
“…Although joint attention is widely accepted as a crucial component of children's first language (L1) development, its role in adult second language (L2) learning remains underexplored. Recent studies have shown that gestures may facilitate the learning of L2 words (Gullberg et al, 2012;Kelly et al, 2009;Macedonia and Knösche, 2011) and new sound contrasts (Hirata and Kelly, 2010;Kelly and Lee, 2012), but the potential role of eye gaze in face-to-face L2 interaction has not been investigated. From Bruner's (Bruner, 1995) socio-pragmatic view of joint attention, which is compatible with both interactionist and emergentist approaches to L2 learning and use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Although joint attention is widely accepted as a crucial component of children's first language (L1) development, its role in adult second language (L2) learning remains underexplored. Recent studies have shown that gestures may facilitate the learning of L2 words (Gullberg et al, 2012;Kelly et al, 2009;Macedonia and Knösche, 2011) and new sound contrasts (Hirata and Kelly, 2010;Kelly and Lee, 2012), but the potential role of eye gaze in face-to-face L2 interaction has not been investigated. From Bruner's (Bruner, 1995) socio-pragmatic view of joint attention, which is compatible with both interactionist and emergentist approaches to L2 learning and use (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…As mentioned earlier, many researchers such as Perdue (1996) Carroll, (2007Carroll, ( , 2012Carroll, ( , 2014, Gullberg et al (2010Gullberg et al ( , 2012, and Rast (2008Rast ( , 2010 amongst many others.…”
Section: )mentioning
confidence: 98%
“…Therefore, different researchers have coined the term describing this area of research differently. For example, it was coined as 'ab initio' by Han and Liu (2013), 'minimal exposure' by Gullberg et al (2010Gullberg et al ( , 2012, and 'first exposure' by Rast (2010) and Carroll (2013Carroll ( , 2014. Throughout this paper, it will be referred to as first exposure of L2.…”
Section: )mentioning
confidence: 99%
See 1 more Smart Citation
“…SLA researchers in the middle of many other scholars have organized L2 research examining the effect of an organized artificial and/or naturalistic input with adult L2 learners to analyze adult L2 learners' input processing abilities. Many studies have also studied first exposure through implicit learning, such as Gullberg, Roberts, andDimroth (2012), andCox (2019). They have examined L1 Dutch learners' first exposure to L2 Mandarin with a realistic input of a 14 minutes Mandarin weather report as the treatment.…”
Section: Figure 2 Traditional View Of Sundanese Vowelmentioning
confidence: 99%